Application of Problem-Based Learning with Video Assistance to The Learning Outcomes of Science from Students in Class V Elementary - Gusmaweti; Rigel Prima Sari; Enjoni (RADINKA JAYA UTAMA PUBLISHER, 2023)
This study aims to determine the effect of the video-assisted Problem-based learning (PBL) model on cognitive and psychomotor aspects of learning outcomes in the question-and-answer indicators in science learning for Class V students at SD Negeri 31 Payakumbuh. This type of research is an experiment with a